Jurisprudential rules in preventing epidemics Hajj in light of the Corona epidemic as a model - Fadhel Ashour Abd Al-Kareem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
As a result of the Corona pandemic, Islamic countries called on Muslims around the world to wait and suspend their preparations for religious rites, including Hajj ceremonies, until further notice until the vision becomes clear.Therefore, the problem of the research is how the abolition of dropping some costs during the pandemic period can be justified from a jurisprudential point of view. Sharia does not accept significant harm, as it has a social and human view.And when the epidemic threatens a person’s health and safety, his mandate and his ability may be waived. For example, the obligation of Hajj is obligatory for the able, but the ability falls when the person in charge of Hajj is a reason for the epidemic to be transmitted to him if the possibility is great.